SEED-BEARING GLOSSOPTERIS LEAVES - Kovacs-Endrody, E. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1974)
Seeds are commonly known elements of Glossopteris floras. The connection of these seeds to any definite elements in the floras and their systematic position with it has always been uncertain, and they are usually referred to as a group "incertae sedis". Several of these seeds have been described and placed in the genera Cardiocarpus Brongniart, Cordiocarpus Geinitz and Samaropsis Goeppert, specially erected for them. Arber (1905, p . 206) noticed the common occurrence of seeds with Glossopteris leaves, and refers to them without any further conclusion as "A few seeds .. . in association with fronds of Glossopteris broumiana. The seeds are possibly referable to Cardiocarpus".